Decolonizing the “state of nature” in political thought - de Wit , Theo (Stellenbosch Theological Journal, 2023)
The study of coloniality as a “social imaginary” (Charles Taylor) from the perspective of decoloniality invites European scholars, to “think again”, to interrogate their own traditions, including their modern political philosophical tradition. In this article, I will discuss a powerful modern political imaginary, namely the democratic narrative of the “social contract”. Such narratives or “imaginations of our origin” (Ursprungsphantasien: Philip Manow) give us answers to the enigma of our social and political existence: what does it mean to live in this political community? What does it give us, ask from us? In the modern narrative of the “social contract”, we are told that, to be a good citizen, we have/had to leave the “state of nature” (status naturalis), a state often described as a state of disorder, conflict, and war, and accept the status of citizenship (status civilis) and a powerful state as guarantee of peace and the rule of law. In this article, I will firstly give some examples of the use of this narrative in very diverse contexts: 1) in the context of the European religious civil wars in the 16th and 17th centuries (birth of the modern liberal political philosophy), 2) in the context of the transition of European nation-states to the European Union after WWII, 3) in the context of the transition of Apartheid South Africa to a non-racial democracy. Secondly, I will concentrate on one of the first philosophers who introduced the state of nature/civil state narrative, Thomas Hobbes (1588–1679), to discover that his political imagination is deeply influenced by the colonial experience in the “New World”, especially the meeting with the indigenous Indians in America. In several aspects, they are in Hobbes’ imagination the incarnation of the life in the “state of nature”. This raises the question, how the idea of a democratic social contract can be reformulated, without Eurocentric and racist premises, and without simply reversing the Hobbesian narrative: since the “colonizer” is the root of our conflict and controversies, to expel him will restore a durable peace.